Do attitudes toward societal structure predict beliefs about free will and achievement? Evidence from the Indian caste system. Issue 1 (5th March 2015) - Srinivasan, Mahesh; Dunham, Yarrow; Hicks, Catherine M.; Barner, David
Abstract: Intuitive theories about the malleability of intellectual ability affect our motivation and achievement in life. But how are such theories shaped by the culture in which an individual is raised? We addressed this question by exploring how Indian children's and adults' attitudes toward the Hindu caste system – and its deterministic worldview – are related to differences in their intuitive theories. Strikingly, we found that, beginning at least in middle school and continuing into adulthood, individuals who placed more importance on caste were more likely to adopt deterministic intuitive theories. We also found a developmental change in the scope of this relationship, such that in children, caste attitudes were linked only to abstract beliefs about personal freedom, but that by adulthood, caste attitudes were also linked to beliefs about the potential achievement of members of different castes, personal intellectual ability, and personality attributes. These results are the first to directly relate the societal structure in which a person is raised to the specific intuitive theories they adopt. Abstract : This figure indicates that Indian adults believe that members of lower castes are more willing to interact with members of higher castes than the reverse, indicating their understanding of the asymmetrical nature of the caste hierarchy. The present study finds that, beginning at least in middle school and continuing into adulthood, individuals who placed more importance on caste were more likely to adopt deterministic intuitive theories. We also found a developmental change in thescope of this relationship, such that in children, caste attitudes were linked only to abstract beliefs about personal freedom, but hat by adulthood, caste attitudes were also linked to beliefs about the potential achievement of members of different castes, personal intellectual ability, and personality attributes.